2018
DOI: 10.1016/j.omtm.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Corrected iPSC-Derived Neural Stem Cell Grafts Deliver Enzyme Replacement to Affect CNS Disease in Sanfilippo B Mice

Abstract: Sanfilippo syndrome type B (mucopolysaccharidosis type IIIB [MPS IIIB]) is a lysosomal storage disorder primarily affecting the brain that is caused by a deficiency in the enzyme α-N-acetylglucosaminidase (NAGLU), leading to intralysosomal accumulation of heparan sulfate. There are currently no treatments for this disorder. Here we report that, ex vivo, lentiviral correction of Naglu−/− neural stem cells derived from Naglu−/− mice (iNSCs) corrected their lysosomal pathology and allowed them to secrete a functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(35 citation statements)
references
References 46 publications
(66 reference statements)
1
34
0
Order By: Relevance
“…We found a significant increase of CD68 and GFAP positive signal in the forebrain of vehicleinjected Naglu −/− mice (Vehicle -/-), compared with control mice (Unaffected +/-) (Fig. 3A, B), data that is consistent with our previous findings 35 . We found a 72-fold increase of the CD68 staining in vehicle-injected mice compared with unaffected ones (p = <0.0001).…”
Section: Effect Of N-igfii-inscs On Glial Activation and Storage Accu...supporting
confidence: 93%
See 1 more Smart Citation
“…We found a significant increase of CD68 and GFAP positive signal in the forebrain of vehicleinjected Naglu −/− mice (Vehicle -/-), compared with control mice (Unaffected +/-) (Fig. 3A, B), data that is consistent with our previous findings 35 . We found a 72-fold increase of the CD68 staining in vehicle-injected mice compared with unaffected ones (p = <0.0001).…”
Section: Effect Of N-igfii-inscs On Glial Activation and Storage Accu...supporting
confidence: 93%
“…Previously, we reprogrammed Naglu -/mouse embryonic fibroblasts into iPSCs and corrected them ex vivo to overexpress the human NAGLU enzyme. We showed that corrected NSCs (N-iNSCs) improved the MPS-associated brain neuropathology in Naglu -/mice 35 . As described above, NAGLU-IGFII is under clinical investigation for ERT.…”
mentioning
confidence: 86%
“…Neonatal mice (both genders) were toe-clipped and genotyped at birth. Sterile-filtered (0.2 μm), purified rhGNS (5 μL; 13.4 or 40.2 units /μL), or vehicle (5 μL) was injected in the left lateral ventricle as previously described . The injection site was ∼2.5 mm between the bregma and eyes, 2 mm away laterally from the sagittal suture, and 2.5 mm in depth.…”
Section: Methodsmentioning
confidence: 99%
“…36 To study mannose 6-phosphorylation of NAGLU in the context of gene therapy, induced pluripotent stem cells derived from Sanfilippo B mouse embryonic fibroblasts were transduced with lentivirus bearing the human NAGLU transgene under a cytomegalovirus promoter. 48 The supernatant from these cells was added to Sanfilippo B patient fibroblasts in the presence or absence of mannose 6-phosphate. The study demonstrated uptake of NAGLU from the supernatant of these lentiviral-modified cells into Sanfilippo B fibroblasts that was nearly completely abolished with the addition of mannose 6-phosphate to the media, suggesting that NAGLU produced by gene therapy may not suffer the same post-translational processing issues as recombinant NAGLU enzyme produced by cells in vitro, as was used in this study.…”
Section: Discussionmentioning
confidence: 99%